2016
DOI: 10.5530/pc.2016.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Extracts from Native Plants of Temperate Australia

Abstract: Introduction: Significant effort has been invested in looking at the antimicrobial activity of plant extracts from tropical regions of Australia, with less interest in those from more temperate environments. We sought to redress this imbalance by examining antimicrobial activities of extracts from native plants of Victoria. Methods: Sixteen plant samples were obtained around the Ballarat region of Victoria. Plant material was desiccated, ground and extracted with methanol at room temperature. Methanol extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…A further 17 % of relevant literature used a water-based extraction protocol, with only three studies using relatively non-polar solvents (diaminopropane, chloroform and acetone). This is consistent with a wide body of research indicating that relatively polar extracted fractions generally contain a greater level of bioactive and antimicrobial compounds compared to their nonpolar counterparts (Han et al, 2007;Tian et al, 2009;Wigmore et al, 2016). This may also be indicative of increased bioactivity of highly polar glycosylated compounds, similar to the vast difference in antiviral activity observed between quercetin and quercetin-7-rhamnoside (Choi et al, 2009).…”
Section: The Significance Of Chemical Polaritysupporting
confidence: 87%
“…A further 17 % of relevant literature used a water-based extraction protocol, with only three studies using relatively non-polar solvents (diaminopropane, chloroform and acetone). This is consistent with a wide body of research indicating that relatively polar extracted fractions generally contain a greater level of bioactive and antimicrobial compounds compared to their nonpolar counterparts (Han et al, 2007;Tian et al, 2009;Wigmore et al, 2016). This may also be indicative of increased bioactivity of highly polar glycosylated compounds, similar to the vast difference in antiviral activity observed between quercetin and quercetin-7-rhamnoside (Choi et al, 2009).…”
Section: The Significance Of Chemical Polaritysupporting
confidence: 87%
“…Recently, antimicrobial activities of methanol extract of M. alternifolia were screened against both Gram‐positive and Gram‐negative species: B. subtilis , L. monocytogenes , M. luteus , S. aureus , E. coli , K. pneumoniae , P. aeruginosa , and S. enterica by broth dilution method. The plant extracts was very active against Gram‐positive bacteria, particularly M. luteus (MIC 0.06 mg/mL) (Wigmore et al ., ). Pseudomonas spp.…”
Section: Melaleuca Spp Plants As Antibacterial and Antifungal Agentsmentioning
confidence: 97%
“…Concentrations of 0. dilution method. The plant extracts was very active against Gram-positive bacteria, particularly M. luteus (MIC 0.06 mg/mL) (Wigmore et al, 2016). Pseudomonas spp.…”
Section: Melaleuca Alternifoliamentioning
confidence: 99%
“…One study reported that a W. fruticosa leaf extract was a potent inhibitor of L. monocytogenes, M. luteus and S. aureus growth in a disc diffusion assay. 26 The same extract was inactive or had only low activity against B. subtilis, E. coli, K, pneumonia P. aeruginosa and S. typhimurium. This contrasts with the results of our current study, which determined that W. fruticosa leaf and flower extracts were completely ineffective against an extended panel of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study reported potent growth inhibitory activity for W. fruticosa leaf extracts against Listeria monocytogenes, Micrococcus luteus and Staphylococcus aureus. 26 The same study reported lower activity or no activity at all against against Bacillus subtilis, Escherichia coli, Klebsiellia pneumonia Pseudomonas aeruginosa and Salmonella typhimurium. In contrast, a different study reported that W. fruticosa leaf and flower extracts were completely ineffective against Aeromonas hydrophilia, Pseudomonas fluorescens, Bacillus cereus and Bacillus subtilis.…”
Section: Introductionmentioning
confidence: 92%